2012
DOI: 10.1509/jm.11.0349
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of Foreign Brand Names for Companies from Emerging Countries

Abstract: Foreign branding—or using brand names that evoke foreign associations through, for example, spelling a brand name in a foreign language—is a popular means in both developed and emerging countries of suggesting a specific country of origin (COO) in the hope that it will evoke certain product qualities. As a result, consumers increasingly encounter products with brand names that imply a COO that differs from the actual COO (where the product is manufactured). In four experiments, the authors find support for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 72 publications
7
113
1
7
Order By: Relevance
“…Consumers process hedonic categories more holistically and therefore may rely on cues such as the brand (Melnyk, Klein, and Völckner 2012). Accordingly, we expect the association of CBBE with SBBE to be stronger in hedonic categories (P1.4 and P2.4).…”
Section: Category Moderators Of the Association Between Cbbe And Sbbementioning
confidence: 93%
“…Consumers process hedonic categories more holistically and therefore may rely on cues such as the brand (Melnyk, Klein, and Völckner 2012). Accordingly, we expect the association of CBBE with SBBE to be stronger in hedonic categories (P1.4 and P2.4).…”
Section: Category Moderators Of the Association Between Cbbe And Sbbementioning
confidence: 93%
“…An increasing number of companies worldwide have adopted the strategy of using foreign brand names in their various markets. (Melnyk, Klein, & Völckner, 2012). Foreign branding defined as, the strategy of spelling or pronouncing a brand name in a foreign language which is targeted primarily toward influencing the brand image dimension of brand equity (LeClerc, Schmitt & Dube, 1994).…”
Section: Foreign Brandingmentioning
confidence: 99%
“…The idea of foreign brand names is to utilize an appropriate, usually category-favorable, country image to influence consumers' evaluations of a product (Melnyk, Klein, & Völckner, 2012). Prior empirical studies have shown that pronunciation in terms of phonetic structure (Yorkston & Menon, 2004), the 'hardness' of consonants (Heath, Chatterjee, & France, 1990), and different vowel sounds (Lowrey & Shrum, 2007) effect consumer impressions of a brand name.…”
Section: Foreign Brandingmentioning
confidence: 99%
“…In emerging markets, most consumers prefer foreign brands because of their favorable country associations (Melnyk, Klein, and Völckner 2012). When a country is considered to have a favorable country image or to possess particular expertise in a product category, brands from that country benefit from the association and have a more favorable brand image (Lee, Lockshin, and Greenacre 2016;Sichtmann and Diamantopoulos 2013).…”
Section: Ibd Of Foreign Versus Domestic Brands In Emerging Marketsmentioning
confidence: 99%